Exploring BIM technology development using patent citation analysis: USA case study - Weng, Kuo-Chan; Chen, Jieh-Haur; Cho, Rico Lee-Ting; Wei, Hsi-Hsien; Yu, Tzuyang (Journal of Civil Engineering and Management, 2025)
Broadening the perspective on technology and stakeholders within the construction sector, this study aims to uncover the trajectories of BIM’s technological progression, alongside the interconnected industries and knowledge networks. Information in Derwent Innovation’s patent database originates from the United States Patent Database (USPTO). Initially, 1,062 patents related to BIM were gathered to form a patent citation network. The subsequent stage of expanding patent citations involved accumulating a total of 9,755 patents. The main path is composed of three streams: Stream I is used for the construction and application of 3D models, Stream II is used for the presentation of 3D images, and Stream III is used for the automatic analysis of architectural information. This study also uses edge-betweenness clustering for cluster analysis and conducts a more in-depth main path study of the specific patent clusters on the main path. These findings are: (1) Energy consumption management control, (2) 3D building modeling for design and construction, (3) Asset tracking, monitoring, and security monitoring. The development of BIM should be directed towards the integration and application of transformative information and communication technologies. Integration with innovative technologies such as the Internet of Things, big data, artificial intelligence, and 5G is an important trend.First published online 20 December 2024